STUDI KOMPARASI JENIS MAKANAN IKAN KEPERAS (Puntius binotatus) DI SUNGAI AEK PAHU TOMBAK, AEK PAHU HUTAMOSU DAN SUNGAI PARBOTIKAN KECAMATAN BATANG TORU TAPANULI SELATAN - Situmorang, Toberni S; Barus, Ternala A; Wahyuningsih, Hesti (Jurnal Perikanan dan Kelautan, 2013)
Research about comparative study of food types of fish Keperas (P. binotatus) inthe river of Aek Pahu Tombak, Aek Pahu Hutamosu and river of Parbotikan DistrictBatang Toru that have aim to determine the types of food in fish and feeding habit ofPuntius binotatus. The research was occured in the river of Aek Pahu Tombak, AekPahu Hutamosu dan river of Parbotikan District Batang Toru in January-March2013.The method of fishing is used by elektrofising gear 12 volt. The analysis of dataincludes the relationship of fish length and weight, condition factor, bulk index (IndexPropenderance), the index of food options, wider food niche, and niche overlap of food.The result showed that fish keperas (P. binotatus) eat 6 groups of organisms that arepresent in all research station, types of Bacillariophyceae is the main food,Chlorophyceae, Monogononta, Ciliophora, and detritus as a supplement food, andCyanophyceae as additives food.